2010
DOI: 10.1161/strokeaha.109.572040
|View full text |Cite
|
Sign up to set email alerts
|

Phase IIB/III Trial of Tenecteplase in Acute Ischemic Stroke

Abstract: Background and Purpose-Intravenous alteplase (rtPA) remains the only approved treatment for acute ischemic stroke, but its use remains limited. In a previous pilot dose-escalation study, intravenous tenecteplase showed promise as a potentially safer alternative. Therefore, a Phase IIB clinical trial was begun to (1) choose a best dose of tenecteplase to carry forward; and (2) to provide evidence for either promise or futility of further testing of tenecteplase versus rtPA. If promise was established, then the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
135
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(144 citation statements)
references
References 10 publications
(7 reference statements)
5
135
1
3
Order By: Relevance
“…Similarly tPA, although proven with IV infusion, may not be the ideal agent for IAT because of some neurotoxic effects resulting in higher rates of ICH [43]. There are multiple reports and small series, some prospective, of the use of other thrombolytics for IAT, including urokinase, reteplase, and tenecteplase, with promising but not definitive results [37,44]. The optimal dose of each thrombolytic is unknown.…”
Section: Intra-arterial Thrombolysismentioning
confidence: 99%
“…Similarly tPA, although proven with IV infusion, may not be the ideal agent for IAT because of some neurotoxic effects resulting in higher rates of ICH [43]. There are multiple reports and small series, some prospective, of the use of other thrombolytics for IAT, including urokinase, reteplase, and tenecteplase, with promising but not definitive results [37,44]. The optimal dose of each thrombolytic is unknown.…”
Section: Intra-arterial Thrombolysismentioning
confidence: 99%
“…Authors concluded that TNK at doses of 0.1 to 0.4 mg/kg are safe in ischemic stroke, and a larger trial was designed. The next trial was funded by the National Institutes of Health and used a sophisticated design that allowed a seamless transition from phase II to III, provided a promising dose was found with adequate safety [63]. The trial began as a phase IIb randomized, double-blinded, and controlled trial that sought the optimal dose of tenecteplase: 0.1, 0.25, or 0.4 mg/kg.…”
Section: Tenecteplasementioning
confidence: 99%
“…However, in a subsequent adaptive sequential design, phase 2B trial enrolling 112 patients, the 0.4 mg kg )1 dose was associated with a high rate of symptomatic haemorrhage and discarded. The trial was prematurely stopped before the 0.1 mg kg )1 or the 0.25 mg kg )1 could be distinguished as the most propitious dose to advance to a phase 3 trial, due to slow enrolment [55]. An on-going Australasian phase 2B study, Tenecteplase in Stroke (TIS) Trial, is comparing tenecteplase at 0.1 and 0.25 mg kg )1 dose tiers with IV tPA, using reperfusion at 24 h as a technical success endpoint.…”
Section: Novel Fibrinolytic Agentsmentioning
confidence: 99%